Interactions between emotions and social context: Basic, clinical and non-human evidence - Sonja A E Kotz (Frontiers Research Topics, 2014)
The emotions that we feel and also those that we perceive in others are crucial to the social functioning of both humans and non-human animals. Although the role of context has been extensively studied in basic sensory processing, its relevance for social cognition and emotional processing is little understood. In recent years, several lines of research at the behavioral and neural levels have highlighted the bidirectional interactions that take place between emotions and social context. Experienced emotions, even when incidental, bias decision-making. Remarkably, even basic emotions can be strongly influenced by situational contexts. In addition, both humans and non-human animals can use emotional expressions strategically as a means of influencing and managing the behavioral response of others in relation to specific environmental situations. Moreover, social emotions (e.g., engaged in moral judgment, empathic concern and social norms) seem to be context-dependent, which also questions a purely abstract account of emotion understanding and expression, as well as other social cognition domains. The present Research Topic of Frontiers in Human Neuroscience highlights the need for a situated approach to emotion and social cognition. We presented theoretical and empirical work at the behavioral and neural levels that contribute to our understanding of emotion within a highly contextualized social realm, and vice-versa. Relevant contributions are presented from diverse fields, including ethology, neurology, biology, cognitive and social neuroscience, and as well as psychology and neuropsychiatry. This integrated approach that entails the interaction between emotion and social context provide important new insights into the growing field of social neuroscience.